Systemic immune-inflammation index as a potential biomarker of cardiovascular diseases: A systematic review and meta-analysis - Ye, Zhen; Hu, Tingyi; Wang, Jin; Xiao, Ruoyi; Liao, Xibei; Liu, Mengsi; Sun, Zhen (Frontiers in Cardiovascular Medicine, 2022)
Background: Several studies have investigated the value of the systemic immune-inflammation index (SII) for predicting cardiovascular disease (CVD), but the results were inconsistent. Therefore, this meta-analysis and systematic review was conducted to assess the correlation between SII and risk of CVD. Methods: Two investigators systematically searched PubMed, Embase, Web of Science, Cochrane library, and CINAHL databases on June 10, 2022 to identify all studies that examined the association between SII levels and CVD. The risk estimates of CVD for people with high SII compared to those with low SII levels and weighted mean difference (WMD) between the CVD and control groups were pooled using fixed- or random-effects models based on heterogeneity test. We used the Newcastle-Ottawa Scale to assess the risk of bias in eligible studies, and the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system was applied to rate the certainty of evidence. Results: A total of 13 studies with 152,996 participants were included for analysis. The overall pooled results showed that higher SII was significantly associated with an increased risk of CVD (HR=1.39, 95% CI: 1.20-1.61, P<0.001). This increased risk could be observed in almost all CVD subtypes, including ischemic stroke (HR=1.31, 95%CI: 1.06-1.63, P=0.013), hemorrhagic stroke (HR=1.22, 95%CI: 1.10-1.37, P<0.001), myocardial infarction (HR=1.11, 95%CI: 1.01-1.23, P=0.027) and peripheral arterial disease (HR=1.51, 95%CI: 1.18-1.93, P=0.001). There were no significant but still similar trends in venous thrombosis (HR=4.65, 95%CI: 0.66-32.71, P=0.122), cerebral small vessel disease (HR=1.09, 95%CI: 0.95-1.25, P=0.233), and acute coronary syndrome (HR=1.08, 95%CI: 0.96-1.22, P=0.200). Furthermore, the pooled results showed that SII levels at the onset of CVD were significantly higher than in the general population (WMD=355.2, 95% CI: 234.8-475.6, P<0.001), which was consistent across different CVD subtypes. The GRADE assessment suggested that the quality of current evidence from observational studies was low or very low. Conclusion: This study indicated that SII may be a potential biomarker for CVD development, but the quality of evidence is generally low. Additional well-designed studies are necessary to determine optimal cutoff values and to characterize the benefited population.